Сутність і зміст поняття “інформаційно-комунікаційні технології” - Данильчук, Лариса (Видавництво Львівської політехніки, 2012)
В статье проведено исследование понятия “информационно-коммуникационные технологии”, их сущность, виды, классификация. Определено, что в профессиональных источниках дефиницию “информационно-коммуникационные технологии” часто отождествляют с информационными технологиями. The article considers the notion of “information and communications technologies”, its essence, types, and classifications. The author mentions that in professional sources the definition of the notion of “information and communications technologies” is considered to be a synonym to the information technologies.
Сущность и содержание понятия “информационно-коммуникационные технологии”
The essence and the contents of the notion of “information and communications technologies”
Keywords: информация; информационная технология; информационно-коммуникационные технологии; средства информационно-коммуникационных технологий; information; information technology; information and communications technologies; means of information and communications technologies